Energy Management Strategy for Shared Battery Energy Storage Systems Considering Economy and SOC Consistency. Issue 1 (1st February 2023) - Li, Hanning; Li, Xiangjun; Chen, Dawei; Li, Zhicheng; Zhang, Weijun; Dong, Lizhi; Deng, Chaoping
Abstract: in an effort to solve the large fluctuation of renewable energy power generation output, which brings many challenges to power system operation, Battery Energy Storage Systems (BESS) are more and more widespread in power systems. This paper proposes an energy management strategy for shared energy storage power plants. First, the shared energy storage power plants are divided into different PCS unit groups, which trade according to different electricity prices. Secondly, the charging and discharging priorities of PCS unit groups are ranked according to the electricity price to maximize the benefits. At the same time, considering the consistency of system SOC (state of charge), the system has higher stability, and more average battery SOC is conducive to better scheduling of BESS. The trade model of a 100MW shared energy storage power station is built in this paper to verify the effectiveness of this method.